Treatment prescribing patterns in patients with juvenile idiopathic arthritis (JIA): Analysis from the UK Childhood Arthritis Prospective Study (CAPS)()() - Davies, Rebecca (Semin Arthritis Rheum, 2016)
OBJECTIVE: Initial treatment of juvenile idiopathic arthritis (JIA) is largely based on the extent of joint involvement, disease severity and ILAR category. The licensing of biologic therapies for JIA has expanded treatment options. The aims of the study are (1) to describe treatment prescribing patterns in JIA over the first 3 years following first presentation to paediatric rheumatology and (2) to determine whether patterns of treatment have changed as biologics have become more widely available. METHODS: Children with at least 3 years of follow-up within the Childhood Arthritis Prospective Study (CAPS) were included. For analysis, children were placed into one of five groups according to their initial presentation to paediatric rheumatology: oligoarthritis (oJIA), polyarthritis (pJIA), systemic (sJIA), enthesitis-related arthritis (ERA) and psoriatic arthritis (PsA). Treatment patterns over 3 years were described. RESULTS: Of 1051 children, 58% received synthetic disease-modifying anti-rheumatic drugs (sDMARD) and 20% received biologics over the 3 years. Use of sDMARDs and biologics was higher in more severe disease presentations (sJIA and pJIA); however, 35% and 10% who presented with oJIA were also treated with sDMARDs and biologics, respectively. The number of children receiving sDMARD after 2006 was higher (p = 0.02); however, there was no difference in biologic prescribing before and after 2006 (p = 0.4). CONCLUSIONS: A high proportion of children presenting with JIA received sDMARDs plus/minus biologics during 3 years of follow-up. This was most common for patients with severe JIA but was also prescribed for patients with oligoarticular disease, despite the lack of evidence for effectiveness in this category.